Perkembangan Pemuliaan Gandum di Indonesia - Nur, Amin; Azrai, Muh.; Subagio, Herman; Soeranto, Soeranto; Ragapadmi, Ragapadmi; Sustiprajitno, Sustiprajitno; Trikoesoemaningtyas, Trikoesoemaningtyas (Puslitbang Tanaman Pangan, 2013)
As a tropical country, Indonesia certainly is not the most suitable place for producing wheat. Wheat flour consumption however, had increased tremendously during the last three decades, that import of wheat grain in 2012 reached 7.2 million ton. Producing wheat had been attempted since 1990’s, utilizing lands at high elevation with drier climate. However, crops competition, especially with the high land vegetables, had put wheat cropping become prohibitive. As early as in 1880, G Wallace experimented of growing wheat in the high land of Timor island. However the crop was never economically established. Selection for genotypes and varieties of wheat for the tropical area had been attempted since 1980’s, and adaptable varieties to the high land had been released, but farmers did not adopt the crop on their cropping system. Breeding research to develop tropical wheat varieties was revived in 2009. By using the modern breeding techniques, including biotechnology, cellular somatic mutation, as well as applying the conventional breeding techniques, varieties adaptable to the lowland tropics are expected to be identified.